Karakterisasi Pertumbuhan Miselia Beberapa Isolat Jamur Merang (Volvariella volvaceae) Hasil Persilangan Tetua Putih dan Tetua Semi sebagai Calon Bibit Sebar di Kabupaten Karawang - Putri, Hilda Wulandari; Lestari, Ani; Sugiono, Darso (UNIVERSITAS LABUHANBATU, 2023)
Straw mushroom (Volvariella volvaceae) is a type of edible mushroom that is quite popular in society.Â Besides its delicious taste and good texture, paddy straw mushroom has rich nutritional content and various benefits for both health and food industry. The paddy straw mushroom production can be increased by using appropriate stocking seeds. This study aimed to obtain Faperta Unsika isolates with the highest mycelium growth on PDA media and baglog (paddy straw). The research was conducted at the Laboratory of the Faculty of Agriculture, Singaperbangsa Karawang University. The research method used is Randomized Block Design (RBD) with five replications. There are seven treatments, namely: A (F3 FP Natural-White), B (F3 FP Semi-White), C (FP038), D (FP039), E (FP040), F (FP041), G (FP043). The effect of treatment is analyzed with analysis of variance and if the F test at the 5% level showed a significant result, then to find out the best treatment, analysis continued with DMRT (Duncan Multiple Range Test) at the 5% level. Treatment D (FP039) gave the highest mycelium colony diameter on PDA media with the average of mycelium colony diameter on 1st, 2nd, and 3rd day after inoculation was 1,18 cm, 4, 75 cm, and 6,93 cm. Treatment E (FP040) and F (FP041) gave the highest mycelium length on baglog media with the highest mycelium was 9,00 cm and 9,20 cm.Â Keywords: isolate faperta unsika, straw mushroom, mycelium